An LMI Approach with Pole Placement Objective for the Design of Robust SSSC Controller for Damping Inter-Area Mode Oscillation Considering Global Signal - J Shah, Bhavin; N Pillai, G; Agarwal, Pramod (International Journal of Engineering and Technology, 2018)
This paper presents robust Static Synchronous Series Capacitor (SSSC) controller design using LMI approach with pole placement objective. The controller is designed for damping of inter-area mode oscillations in two area four machine test system considering a global signal. The control signals are obtained from wide area measurements (WAMs) system. Residue analysis is performed to decide best input signal to the controller. The mixed sensitivity approach in Linear Matrix Inequality (LMI) formulation is used to design thedamping controller. The uncertainty in load model composition results in the inaccurate estimation of the designed controller capability. So, different load model compositions including static and dynamic loads are considered here. Various contingency conditions are applied for testing the designed controller. The designed controller provides sufficient damping for such contingent conditions.Â Â